2012
DOI: 10.1088/0963-0252/22/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of nanosecond-pulse electrical discharges

Abstract: Recent experiments with a nanosecond-pulse, dielectric barrier discharge at the stagnation point of a Mach 5 cylinder flow have demonstrated the formation of weak shock waves near the electrode edge, which propagate upstream and perturb the bow shock. This is a promising means of flow control, and understanding the detailed physics of the conversion of electrical energy into gas motion will aid in the design of efficient actuators based on the concept. In this work, a simplified configuration with planar symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 63 publications
0
58
0
Order By: Relevance
“…This is in contrast to the behavior of the dielectric surface which does not readily give up electrons. Modeling and simulation of nanosecond pulse discharges are a subject of current research [26][27][28][29][30][31][32][33][34][35][36][37] and the exact kinetic mechanisms responsible for near-surface gas heating and subsequent aerodynamic flow control are not completely clear. However, the importance of electrons as a driver for this process is generally accepted and supports the suggestion in this paper regarding the role of the exposed electrode.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the behavior of the dielectric surface which does not readily give up electrons. Modeling and simulation of nanosecond pulse discharges are a subject of current research [26][27][28][29][30][31][32][33][34][35][36][37] and the exact kinetic mechanisms responsible for near-surface gas heating and subsequent aerodynamic flow control are not completely clear. However, the importance of electrons as a driver for this process is generally accepted and supports the suggestion in this paper regarding the role of the exposed electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Classical boundary conditions were employed for plasma model. On the surface of upper electrode and dielectric barrier, second electron and electron energy emission were considered: Γeboldn=αs"μeneboldEαsiγifalse(boldΓionnfalse) Γϵn=(5/3)ϵΓenϵwiγifalse(Γibold-italicnfalse) Γion,nbold-italicn=αsμionnionbold-italicE where α s and α ′ s (=− α s ) is the switch function and is equal to 0 when the ion flow is away from the surface, else equal to 1. γ i , the secondary electron emission coefficient, is set as 0.05, same as that in Ref . It has to be mentioned that, the secondary electron emission coefficient is set as a constant value, as currently there hasn't been a systematical and deep insight into the mechanism on how this value will affect nanosecond pulsed plasma discharge .…”
Section: Two‐dimensional Plasma‐fluid Coupled Model Of Npdbd Plasma Amentioning
confidence: 99%
“…where a s and a 0 s (¼Àa s ) is the switch function and is equal to 0 when the ion flow is away from the surface, else equal to 1. g i , the secondary electron emission coefficient, is set as 0.05, same as that in Ref. [20][21][22][23] It has to be mentioned that, the…”
Section: Parameters Of Plasma Actuator and Voltage Pulsementioning
confidence: 99%
“…This assumption may be reevaluated in future work, but it is unlikely that its inclusion into the model will strongly influence the formation of the subsequent compression wave, given that the ion wind would induce a transverse velocity (in contrast to the upstream traveling compression wave). In addition, recent high-fidelity 1-D computations [22] of the ns-DBD showed that the device created a very small region of relatively high ion density and electric field required for the ion wind effect, and that the very high electric field only existed for a short period of time prior to space-charge shielding suppressing the ion wind. As such, acceleration of neutral particles through ion-neutral collisions was very limited, and the majority of the fluid motion was associated with rapid thermal energy transfer into the translational energy mode.…”
Section: Methodsmentioning
confidence: 99%